Insights into hominin phenotypic and dietary evolution from ancient DNA sequence data. Issue 79 (February 2015) - Perry, George H.; Kistler, Logan; Kelaita, Mary A.; Sams, Aaron J.
Abstract: Nuclear genome sequence data from Neandertals, Denisovans, and archaic anatomically modern humans can be used to complement our understanding of hominin evolutionary biology and ecology through i) direct inference of archaic hominin phenotypes, ii) indirect inference of those phenotypes by identifying the effects of previously-introgressed alleles still present among modern humans, or iii) determining the evolutionary timing of relevant hominin-specific genetic changes. Here we review and reanalyze published Neandertal and Denisovan genome sequence data to illustrate an example of the third approach. Specifically, we infer the timing of five human gene presence/absence changes that may be related to particular hominin-specific dietary changes and discuss these results in the context of our broader reconstructions of hominin evolutionary ecology. We show that pseudogenizing (gene loss) mutations in the TAS2R62 and TAS2R64 bitter taste receptor genes and the MYH16 masticatory myosin gene occurred after the hominin-chimpanzee divergence but before the divergence of the human and Neandertal/Denisovan lineages. The absence of a functional MYH16 protein may explain our relatively reduced jaw muscles; this gene loss may have followed the adoption of cooking behavior. In contrast, salivary amylase gene ( AMY1 ) duplications were not observed in the Neandertal and Denisovan genomes, suggesting a relatively recent origin for the AMY1 copy number gains that are observed in modern humans. Thus, if earlier hominins were consuming large quantities of starch-rich underground storage organs, as previously hypothesized, then they were likely doing so without the digestive benefits of increased salivary amylase production. Our most surprising result was the observation of a heterozygous mutation in the first codon of the TAS2R38 bitter taste receptor gene in the Neandertal individual, which likely would have resulted in a non-functional protein and inter-individual PTC (phenylthiocarbamide) taste sensitivity variation, as also observed in both humans and chimpanzees.